Epistemologi Filsafat Hukum Keluarga dalam Rekonstruksi Pemikiran Normatif pada Masyarakat Modern - Rahmad Sujud Hidayat; Achmad Kholiq; Yudi Rijali Muslim (Jurnal Ekonomi, Bisnis dan Humaniora (EKSISHUM), 2025)
The epistemology of the philosophy of family law is an in-depth study of the basics of knowledge, sources of truth, and legal legitimacy that govern family relations in society. In the modern context, social, cultural, and technological dynamics demand a reconstruction of normative thinking in order to keep family law relevant. This paper seeks to analyze the epistemological framework of the philosophy of family law by linking normative traditions, positive law, and universal morality principles. The research method used is a literature study with a philosophical-normative approach. The results of the study show that the epistemology of family law must be based on rationality, the value of justice, and sensitivity to social change. Thus, modern family law needs to be continuously reconstructed to maintain a balance between traditional values and the needs of contemporary society.